2006
DOI: 10.1111/j.1600-0765.2006.00897.x
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring periodontal disease status in smokers and nonsmokers using a gingival crevicular fluid matrix metalloproteinase‐8‐specific chair‐side test

Abstract: Persistently elevated GCF MMP-8 concentrations may indicate sites at risk, as well as patients with poor response to conventional periodontal treatment (e.g. SRP). MMP-8 testing may be useful as an adjunct to traditional periodontal diagnostic methods during the maintenance phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
173
1
10

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(198 citation statements)
references
References 39 publications
(66 reference statements)
14
173
1
10
Order By: Relevance
“…En la actualidad ya existen algunos dispositivos de uso en clínica para determinar experimentalmente los niveles de estos biomarcadores, particularmente para la MMP-8. Al respecto se ha visto que las variaciones en los niveles de esta enzima pueden diferenciar sujetos sanos, de sujetos con gingivitis y periodontitis, como también evaluar la respuesta al tratamiento periodontal e identificar sujetos en riesgo de progresión (26)(27)(28) . De este modo, una herramienta no invasiva para detectar la presencia de inflamación periapical como el FCG sería de gran utilidad como complemento a la evaluación clínico-radiográfica de dientes con PAA, particularmente en aquellos casos en que la interpretación radiográfica sea incierta (29) .…”
Section: Discussionunclassified
“…En la actualidad ya existen algunos dispositivos de uso en clínica para determinar experimentalmente los niveles de estos biomarcadores, particularmente para la MMP-8. Al respecto se ha visto que las variaciones en los niveles de esta enzima pueden diferenciar sujetos sanos, de sujetos con gingivitis y periodontitis, como también evaluar la respuesta al tratamiento periodontal e identificar sujetos en riesgo de progresión (26)(27)(28) . De este modo, una herramienta no invasiva para detectar la presencia de inflamación periapical como el FCG sería de gran utilidad como complemento a la evaluación clínico-radiográfica de dientes con PAA, particularmente en aquellos casos en que la interpretación radiográfica sea incierta (29) .…”
Section: Discussionunclassified
“…This finding suggests that host response during gingivitis might be heterogeneous and some of the inflammatory phenotypes could be more susceptible to periodontitits development . Accordingly, elevation of active MMP-8 has previously been associated with the conversion of gingivitis to periodontitis and established periodontitis (Mantyla et al, 2006). Despite MMP-13 has been more related to chronic periodontitis progression than severity of inflammation, it has previously been reported that MMP-13 also increase progressively from healthy subjects to periodontitis in GCF.…”
Section: Matrix Metalloproteinases (Mmps) In Gingivitismentioning
confidence: 97%
“…These procedures, as well as GCF sampling, are technically demanding and the GCF volume can be very small (1-5 µl). Despite these apparent diagnostic and technical disadvantages, GCF is still considered as a candidate potential oral fluid for the development of adjunctive non-invasive chair-side point of-care diagnostic technology (Sorsa et al 1999;Sorsa et al 2006;Sorsa, Tjaderhane, and Salo 2004;Mantyla et al 2006;Mantyla et al 2003;Munjal et al 2007), especially because tissue destructive MMPs and their bioactive regulators can conveniently be measured by distinct catalytic and non-catalytic immunoassays from GCF ).…”
Section: Oral Fluid Chair-side Point-of-care Technologies and Their Smentioning
confidence: 99%
“…During a study period, it is likely that only a small number of sites with AL can be confirmed. Additionally, only a small group of periodontitis patients manifest multiple progressing sites (Chambers et al 1991;Mantyla et al 2006). In our previous study, we could not make a conclusion about the predictive value of MMP-8 testing .…”
Section: Oral Fluid Chair-side Point-of-care Technologies and Their Smentioning
confidence: 99%
See 1 more Smart Citation